su-Based Shaft Friction Design Method and Evaluation for Pipe Pile - Bin Huang; Yuting Zhang; Xudong Fu; Ruiyu Ye (Advances in Materials Science and Engineering)
The shaft friction in clay is essential to bearing capacity of pipe piles. Reasonable selection of design methods and parameters is very important for offshore piles. This paper focuses on the current popular vertical load design methods based on undrained strength for pipe piles, especially for offshore piles. Based on the database, the accuracy and reliability of various pile design methods based on undrained strength su in clay were reviewed. The small-scale model tests were conducted to evaluate su-based methods. For the shortcomings of small-diameter piles in the database, a field test of full-scale offshore pile was carried out and analysed. By comparing the calculated and the measured capacity for each method, the reliability of various design methods is evaluated for large-diameter piles. For the design methods based on undrained strength, it demonstrates the importance and reliability of the determination of undrained strength parameters. In view of the vertical loading conditions of offshore large-diameter steel pipe piles, reasonable suggestions for design methods and parameters determination are given.